A Young Girl With Granulomatosis with Polyangiitis: A Rare Case Report - Rahman, Md Mahfuzer; Roy, Rana Shankor; Rabbani, Md Golam; Banu, Akter; Kabir, Md Jahangir; Azad, Md Abul Kalam; Akter, Mohsina; Arafat, Yeasir (Bangladesh Journal of Medicine, 2023)
Granulomatosis with polyangiitis (GPA), formerly known as Wegener's granulomatosis is a necrotizing vasculitides that primarily affects small-sized arteries and manifests differently depending on the organ involved and the severity of the disease. Here we are reporting a case of a 15-year-old girl presented with purulent nasal discharge with epistaxis, cough, reduced hearing, fever & rash. Tissue biopsy report, positive C-ANCA, imaging and clinical features were consistent with the diagnosis of GPA. After counseling the patient & her parents and taking consent, she has been treated with intravenous methylprednisolone and cyclophosphamide. Despite being a rare disease with a typical age of onset around 40 years, it should be suspected in any aged patient exhibiting constitutional symptoms and other evidence of upper or lower respiratory tract involvement or glomerulonephritis. Bangladesh J Medicine 2023; 34(2): 151-154